Measurement of Markers of Activated Coagulation in Antithrombin III Deficient Subjects - Demers, Christine; Ginsberg, Jeffrey S; Henderson, Penny; Ofosu, Fred A; Weitz, Jeffrey I; Blajchman, Morris A (Thrombosis and Haemostasis, 1992)
Functional antithrombin III levels were measured by factor Xa inhibition in 63 members of a large family with type 2 antithrombin III deficiency and individuals were classified as antithrombin III deficient or non-deficient according to the results. FI+2 and TAT complexes were measured using an ELISA and FPA levels were measured by radioimmunoassay.Thirty subjects (48%) were classified as antithrombin III deficient and 33 (52%) as antithrombin III non-deficient. The mean level of FI+2 was significantly higher in the deficient adults (0.87 ± 0.26) compared to both the non-deficient adults (0.70 ± 0.21) (p = 0.03) and the deficient adults receiving warfarin (0.16 ± 0.01) (p <0.001). The differences in the mean values of TAT complexes and FPA between deficient and non-deficient individuals were not statistically significant.These findings suggest that untreated antithrombin III deficient subjects generate more thrombin than their non-deficient family members and that warfarin inhibits this thrombin formation. In this cross-sectional study, it is not possible to correlate the levels of the surrogate makers with future clinical outcome.